2009
DOI: 10.1007/s00702-009-0325-7
|View full text |Cite
|
Sign up to set email alerts
|

Elevated serum homocysteine level is not associated with serum C-reactive protein in patients with probable Alzheimer’s disease

Abstract: Elevated plasma homocysteine (Hcy) levels have been associated with Alzheimer's disease (AD) and cognitive impairment. Studies have shown that Hcy may have direct and indirect neurotoxicity effects. The aim of the study was to investigate serum Hcy concentration in patients with probable AD with age-matched controls and to determine whether there was an association between serum Hcy and C-reactive protein concentration in patients with probable AD. We also aimed to determine whether there was an association be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…A significant negative relationship was found only between serum tHcy levels and MMSE scores in n-ADP. Other researchers have also shown a significant negative association between serum tHcy concentration and cognitive impairment tested by the MMSE score in patients with probable AD [15]. Although some studies found no association between plasma tHcy levels and cognitive impairment in patients with AD [16], in the presented study, the mean serum tHcy concentrations for AD and n-AD patients were elevated in comparison to upper reference limits for tHcy (20 µmol/l) in patients aged >65 years, and in comparison to control, but no statistically significant differences were noted.…”
Section: Discussionmentioning
confidence: 84%
“…A significant negative relationship was found only between serum tHcy levels and MMSE scores in n-ADP. Other researchers have also shown a significant negative association between serum tHcy concentration and cognitive impairment tested by the MMSE score in patients with probable AD [15]. Although some studies found no association between plasma tHcy levels and cognitive impairment in patients with AD [16], in the presented study, the mean serum tHcy concentrations for AD and n-AD patients were elevated in comparison to upper reference limits for tHcy (20 µmol/l) in patients aged >65 years, and in comparison to control, but no statistically significant differences were noted.…”
Section: Discussionmentioning
confidence: 84%
“…Overall, an inverse correlation was found between the MMSE scores and the plasma Hcy levels in cases (39)(40)(41)(42). Similarly, Kim and colleagues showed a significant negative relationship between the plasma Hcy levels and the scores of the Word List Memory and Constructional Recall (WLMCR) test in the AD group, after adjusting for several covariates.…”
Section: Alzheimer´s and Cognitive Impairmentmentioning
confidence: 87%
“…Given that the association with AD may well be weaker than with cardiovascular disease, this emphasizes the gap between finding an association with disease and proof of utility as a biomarker. Nonetheless, CRP and tHcy may have independent effects on the risk of developing AD [51] and an elevation in CRP has been associated with AD, rate of progression of AD, MCI and Down’s syndrome [39,5257]. However, other large longitudinal studies found that other general markers of inflammation, such as TNF-α but not CRP, were associated with risk of dementia or with brain volume [58,59] and others found an association between CRP and vascular dementia [60].…”
Section: Candidate Plasma Biomarkers: Single Proteinsmentioning
confidence: 99%